THE MOBILE SMART WATER SUPPLY INFRASTRUCTURE POWERED BY RENEWABLE ENERGY IN ERRABU VILLAGE, SUMENEP, MADURA, INDONESIA - Rahmanto, Ach. Desmantri; Hopid, Hopid; Chayati, Cholilul; Setiawan, Muhammad Ikhsan; Kamisutara, Made; Prawito, Adi (LPPM of NAROTAMA UNIVERSITY, 2024)
The mobile smart water supply infrastructure powered by renewable energy in Errabu Village, Sumenep, Madura, Indonesia, aims to enhance agricultural food security. This system integrates smart technology and renewable energy to optimize water resource management and support agriculture in impoverished and underdeveloped areas. Mobile and Smart Concept, allows flexibility in water distribution, enabling access to hard-to-reach areas. Utilizes sensors and IoT devices to monitor and manage water usage efficiently. Renewable Energy, utilizes solarenergy to operate the water supply system, reducing dependence on fossil fuels. Enhances sustainability by reducing carbon emissions and environmental impact. Solutions for Dry Land, employs water-saving drip or sprinkler irrigation technology to boost productivity in dry lands. Optimizes water usage for agriculture, thereby increasing yields on previously unproductive land. Food Security, with better access to water, farmers can enhance their agricultural output, contributing to local food security. Enables farmers to grow a variety of crops, increasing food diversity and income. Social and Economic Impact, enhances the capacity of local farmers through training and access to new technologies. By improving agricultural yields, it is expected to reduce poverty levels in the village. Implementation and Collaboration, collaboration between the government, educational institutions, and the community is necessary to design and implement this system. Seeking funding sources from the government or donor agencies to support the development of this infrastructure.